Population Status and Conservation Efforts of Bos frontalis (Mithun) in Adi Tribe Inhabited Areas of Arunachal Pradesh, India - Apum, Nayo; Nimasow, Gibji; Nimasow, Oyi Dai; Bapu, Tashi Dorjee; Bushi, Dhoni (National Geographical Journal of India, 2022)
Mithun (Bos frontalis) is a semi-wild animal which is highly priced among the tribal people of Arunachal Pradesh. This rare livestock is facing threats of extinction. In this paper, attempt has been made to know the population status and the prevailing conservation efforts of Mithun in the area. Aquestionnaire-based survey was carried out covering the households possessing Mithuns. The study found a good number of Mithunsin the area. However, a declining population trend was observed due to its multiple uses in social, economic, cultural and political life of the people. As it is associated with their culture, there is a rising concern among the people for its conservation. Conservation initiatives by the Adi Baane Kebang, Adi Cultural and Literary Society and Adi Students Union have been discussed and interpreted. Finally, constructive suggestions have been made for ensuring future sustainability of the species.